Pervasive enough? General purpose technologies as an emergent property - Vladimir Korzinov; Ivan Savin (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2016)
We propose a novel model of knowledge discovery shedding light on the emergence of General Purpose Technologies (GPTs), the process which has been largely neglected in the literature on technological change. We demonstrate that GPTs emerge only when certain conditions with regard to the following techno-economic factors are met: knowledge diffusion, coordination on technological trajectories and volatility in the rank of expected returns on products. Furthermore, our model provides intuitive explanation for technological lock-ins, S-shaped curves of technology adoption, temporal clustering of innovations in time and replicates distinct features of empirical networks of relatedness among technologies and products.
urn:nbn:de:swb:90-620136
Keywords: C63; D83; D85; L16; O3; 330; general purpose technology; technology networks; pervasiveness of technologies; knowledge diffusion; innovation